KEBIJAKAN PEMERINTAH ITALIA TERHADAP IMIGRAN - Fiernaya, Monica; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research will explain about Italia policies regarding immigrants especially in time of immigrant crises that happened, Italia geography position that is near to Mediterranian Sea put Italia as a target of migrants for seeking a better live and leave their origin country. As a result, migrants flow to Italy keep increasing and hard to control, the disagreement and the unbalance responsibilities that given from European Union to its member to similize the policies in response to migrants. It requires Italia to take a policy to tighten up immigrants to get into their territory and stricter their rules. This research also usesÂ library research methods and qualitative methods. This research use library research methods and qualitative research. This analyses use unit/state level analysis, the using of securitization theory due to the emergence of security agenda that is occurred. Constructivism perspective is also use in this research to anaylize the phenomenon that occurs, this perspective is use due to Italia policies is the result of European Union regime and stigmatization towards immigrant.However, Italia policies related in border control and also in managing overflow migrants result in dilemma, the unability of European Union and disagreement in European Union regime of the countries that become the main spurpose of the migrant that suffers. Â Â Key words: Immigrants, Italia, Mediterranian Sea, European Union Agreement